A spintronic analog of the Landauer residual resistivity dipole on the surface of a topological insulator containing a line defect. (25th January 2023) - Fabiha, Raisa; Bandyopadhyay, Supriyo
Abstract: The Landauer 'residual resistivity dipole' is a well-known concept in electron transport through a disordered medium. It is formed when a defect/scatterer reflects an impinging electron causing negative charges to build up on one side of the scatterer and positive charges on the other. This charge imbalance results in the formation of a microscopic electric dipole that affects the electrical resistivity of the medium. Here, we show that an equivalent entity forms in spin polarized electron transport on the surface of a real topological insulator (TI) such as Bi2 Te3 containing a line defect. When electrons reflect from such a scatterer, a local spin imbalance forms owing to spin accumulation on one side and depletion on the other side of the scatterer, resulting in a spin current that flows either in the same or in the opposite direction as the injected spin current, and hence, either decreases or increases the spin resistivity . Spatially varying local magnetic fields appear in the vicinity of the scatter, which will cause transiting spins to precess and emit electromagnetic waves. If the current injected into the TI is an alternating current, then the magnetic field's polarity will oscillate in time with the frequency of the current and if the spins can follow quasi-statically, then they will radiate electromagnetic waves of the same frequency, thereby making the scatterer act as a miniature antenna.